A home in the city : improving the lives of slum dwellers : [achieving the Millennium development goals] - Garau, Pietro; Sclar, Elliott D.; Carolini, Gabriella Y. (UN millennium project 2005, 2005)
More than 900 million people currently live in urban slums and the number is growing as rapid urbanization continues in the developing world. A Home in the City urges countries to strengthen their focus on the growing urban crisis and improving the lives of slum dwellers. Proposed are specific investments and policy changes required at local and national levels to create a vibrant, equitable and productive urban environment. It underscores the need for close strategic partnerships between local authorities and organizations of the urban poor for slum upgrading and improved urban management.